Starch – carrageenan based low-cost membrane permeability characteristic and its application for yeast microbial fuel cells - Christwardana, Marcelinus; Kuntolaksono, Satrio; Septevani, Athanasia Amanda; Hadiyanto, H (International Journal of Renewable Energy Development, 2024)
Microbial fuel cells (MFCs) are an innovative method that generates sustainable electricity by exploiting the metabolic processes of microorganisms. The membrane that divides the anode and cathode chambers is an important component of MFCs. Commercially available membranes, such as Nafion, are both costly, not sustainable, and harmful to the environment. In this study, a low-cost alternative membrane for MFCs based on a starch-carrageenan blend (SCB-LCM) was synthesized. The SCB-LCM membrane was created by combining starch and carrageenan and demonstrated a high dehydration rate of 98.87 % over six hours. SEM analysis revealed a smooth surface morphology with no pores on the membrane surface. The performance of SCB-LCM membrane-based MFCs was evaluated and compared to that of other membranes, including Nafion 117 and Nafion 212. All membranes tested over 25 hours lost significant weight, with SCB-LCM losing the least. The maximum power density (MPD) of the SCB-LCM MFCs was 15.77 ± 4.34 mW/m2, indicating comparable performance to commercial membranes. Moreover, the cost-to-power ratio for MFCs employing SCB-LCM was the lowest (0.03 USD.m2/mW) when compared to other membranes, indicating that SCB-LCM might be a viable and cost-effective alternative to Nafion in MFCs. These SCB-LCM findings lay the groundwork for future research into low-cost and sustainable membrane for MFC technologies.